Problems faced by Pakistani Muslim women in peace and reform and their solution in the light of Islamic teachings: پاکستانی مسلم خواتین کو امن و اصلاح میں در پیش مسائل اور اسلامی تعلیمات کی روشنی میں ان کا حل - Khan, Dr. Muhammad Majid; Hassan, Dr. Muhammad Zubair; Haq, Dr. Inam ul (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Human’s life cycle began with a man and a woman. The women breed the human race with her blood and children’s care, home management, preparation of food and clothes have been remained in her duties. Peace is the substitute of security and reformation is the name of correction. So, it must be in view that where Islam wants collective reform, it never ignores person’s correction but it declares that man’s correction is truly a social reform. No doubt, the feminist part is called a spinal cord of society, if they come forward in this field to improve the work of reform, unite each other with the concept of every correction, the destination of our society will be reversed. In reality, the society will become a practical model of peace then it can be called a reformed and welfare community. This article will highlight, the problems related to Muslim women in peace and reform in Pakistan with their solutions in the light of Quran and Sunnah.